Emotional Intelligence and its Relationship to Self-disclosure among Mut’ah University Students - Al Talahin, Fatima Mohammad (Journal of Ecohumanism, 2025)
The research investigated emotional intelligence levels and their relationship to self-disclosure practices among Mut’ah University students. The research sample included (220) university students made up of (131) males and (89) females from the first semester at Mut’ah University in the academic year 2021/2022. The study employed available sampling to choose participants while employing correlational description as its research approach with emotional intelligence and self-disclosure scales. The studied participants disclosed information at a moderate level while revealing the least details about their physical aspects (3.55) yet sharing the most personal information regarding their social life (3.74). The observed mean values were situated in the medium range of (3.74). The ratings of emotional intelligence (EI) showed positive growth because emotion management reached (4.19) and the total EI score reached (3.75) at high levels. All research studies demonstrated that women showed superior emotional intelligence and better self-disclosure abilities. The study revealed that students from upper academic years and females demonstrated higher self-disclosure than other students. The emotional intelligence test results showed a wide gender difference because women scored better than men. Students who share their emotions freely with others develop higher emotional intelligence levels because self-disclosure shows a strong positive connection to emotional growth.